COVID-19: Coronavirus Vaccine Development Updates - Zhao, Jing; Zhao, Shan; Ou, Junxian; Zhang, Jing; Lan, Wendong; Guan, Wenyi; Wu, Xiaowei; Yan, Yuqian; Zhao, Wei; Wu, Jianguo; Chodosh, James; Zhang, Qiwei (Frontiers in Immunology, 2020)
Coronavirus Disease 2019 (COVID-19) is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), a newly emerged coronavirus, which has been pandemic since March 2020 and led to lots of fatalities. Vaccines are the most efficient means to control and stop the pandemic of COVID-19. However, currently there is no effective COVID-19 vaccine approved and used worldwide except for two human adenovirus vector vaccines for limited use in China and Russia. The safe and effective vaccines against COVID-19 are in urgent need. Researchers around the world are developing 203 COVID-19 vaccines, and 32 vaccines are in human trials. In this review, we summarized and analyzed the current vaccine progress against SARS-CoV, Middle East Respiratory Syndrome Coronavirus (MERS-CoV), and SARS-CoV-2, including inactivated vaccines, live attenuated vaccines, subunit vaccines, virus like particles, nucleic acid vaccines and viral vector vaccines, etc., aiming to provide a reference for COVID-19 vaccine development.